SPE Annual Technical Conference and Exhibition 1991
DOI: 10.2118/22845-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Laboratory Investigation of Microbial Transport Phenomena in Porous Media

Abstract: Simulation and experimental results on the transport of microbes and nutrients in one-dimensional coreflooding experiments are presented, and the development of a three-dimensional, three-phase, multiple-component numerical model to describe the microbial transport phenomena in porous media is described. The governing equations in the mathematical model include net flux of microbes by convection and dispersion, decay and growth rates of microbes, Chemotaxis and nutrient consumption, and deposition of microbes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Bacteria and substrate are continuously injected into the reservoir with the same rate. In the literature related to both enhanced oil recovery and wastewater treatment, many different injection concentrations are used ranging from 10 −5 to 10 kg of substrate per cubic meter [10,14,56,59,61]. We have chosen a substrate mass fraction from the higher concentration range.…”
Section: Parameters and Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria and substrate are continuously injected into the reservoir with the same rate. In the literature related to both enhanced oil recovery and wastewater treatment, many different injection concentrations are used ranging from 10 −5 to 10 kg of substrate per cubic meter [10,14,56,59,61]. We have chosen a substrate mass fraction from the higher concentration range.…”
Section: Parameters and Initial Conditionsmentioning
confidence: 99%
“…MEOR models have been developed with different selections of mechanisms of bacterial actions [10,14,37,40,51]. However, as mentioned earlier, the main contribution to the additional oil recovery originates from in situ surfactant production and the selective plugging effect.…”
Section: Introductionmentioning
confidence: 99%
“…Growth rate expressions for microorganisms are often the Monod expression based on the Michaelis-Menten enzyme kinetics and Langmuir expressions for heterogeneous catalysis (Chang et al 1991;Islam 1990;Nielsen et al 2003;Zhang et al 1992). The Monod expression is widely used, but it is still empirical regarding microbial growth.…”
Section: Bacterial Growth Consumption and Productionmentioning
confidence: 99%
“…Porosity and permeability were changed due to deposition of microorganisms. Chang et al (1991) demonstrated that the oil recovery increased by microbial plugging. Behesht et al (2008) have developed a MEOR model, where several mechanisms are taken into account; surfactant production and adsorption, salinity effects, adsorption of microorganisms, reduction of interfacial tension, and wettability changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation